Effects of Poultry Manure on Watermelon (Citrullus lanatus) Production and Insect Infestation in a Humid Ecological Zone - Awah, Grace O.; Atijegbe, Sylvester R.; Zakka, Usman; Lale, Ndowa E. S. (Jordan Journal of Agricultural Sciences, 2024)
A field trial was conducted to evaluate the effect of poultry manure (PM) on the growth, yield, and infestation of insect pests of watermelon. There were five treatments namely; 1.25 tons of PM ha-1, 2.5 tons of PM ha-1, 5 tons of PM ha-1, 300kg of NPK ha-1, and an untreated control with three replications, which were laid out in a Randomized Complete Block Design. Data on vine length, stem girth, number of leaves, fruit weight, days to 50% emergence, days to 50% flowering, and number of insects were recorded. The results showed that there were no significant differences in the vine length, stem girth, number of leaves, fruit weight, and 50% emergence. However, there were significant differences in vine length at week 3 and week 4, stem girth at week 3, 50% days to flowering, and week 1 for insect population between the 1.25 tons of PM ha-1 and control. The study showed that C. lanatus can be economically grown in the humid ecological zone (October-January) and poultry manure at the rate of 1.25 tons of PM ha-1 was optimal for its cultivation